2019
DOI: 10.1038/s41598-019-42211-z
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly nanocomposites derived from geranium oil and zinc oxide in one step approach

Abstract: Nanocomposites offer attractive and cost-effective thin layers with superior properties for antimicrobial, drug delivery and microelectronic applications. This work reports single-step plasma-enabled synthesis of polymer/zinc nanocomposite thin films via co-deposition of renewable geranium essential oil-derived polymer and zinc nanoparticles produced by thermal decomposition of zinc acetylacetonate. The chemical composition, surfaces characteristics and antimicrobial performance of the designed nanocomposite w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 76 publications
1
32
0
1
Order By: Relevance
“…Surfaces functionalized with enzymes, antibiotics and biocides have also been used in the effort to combat microbial attachment [11][12][13]. Hydrophilic/hydrophobic modification and immobilization of nanoparticles (Nps), such as Cu, ZnO, and Ag, onto the surface of material have been used separately as an effective strategy to reduce biofilm formation [14][15][16][17][18]. Surfaces modified to display hydrophilic behavior have shown superior antifouling properties [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Surfaces functionalized with enzymes, antibiotics and biocides have also been used in the effort to combat microbial attachment [11][12][13]. Hydrophilic/hydrophobic modification and immobilization of nanoparticles (Nps), such as Cu, ZnO, and Ag, onto the surface of material have been used separately as an effective strategy to reduce biofilm formation [14][15][16][17][18]. Surfaces modified to display hydrophilic behavior have shown superior antifouling properties [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the resultant packaging can serve to improve the distribution logistics and food preservation [48]. For instance, Al-Jumaili et al [49] developed nanocomposite films combining renewable geranium essential oil (GEO) with ZnO. These sustainable nanocomposite films were proposed as active coatings of medical devices.…”
mentioning
confidence: 99%
“…The atomic force microscopy image (AFM) in Figure 2e shows that the pristine polymer was uniform and smooth, with an average roughness of 0.25 nm for an input power of 10 W. In contrast, composite films revealed a porous surface, as seen in Figure 2e, with a random distribution of ZnO NPs, where the average roughness was at 33.7 ± 2.1 nm for the input power of 10 W. SEM and AFM data were briefly presented in this report only to demonstrate that the material contained ZnO NPs with antimicrobial properties. A more in-depth investigation of the release of ZnO NPs and morphological, surface, chemical, and antimicrobial properties of Zn/Ge composites films can be found in our previous report [13].…”
Section: Resultsmentioning
confidence: 99%
“…The development of multifunctional surface coatings that reveal both insulation and antimicrobial properties could be accomplished through the use of metal/polymer nanocomposite films. In our previous study [13], a novel nanocomposite film was fabricated from ZnO nanoparticles (NPs) and renewable geranium oil using a single-step plasma-enabled approach. We demonstrated that a significant antibacterial activity could be achieved by incorporating a low concentration (~1%) of zinc oxide nanoparticles into inherently antibacterial geranium thin films [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation